Management of Loyalty and Its Main Antecedents in Sport Organizations: A Systematic Analysis Review - Loranca-Valle, Cristina; Cuesta-Valiño, Pedro; Núnez-Barriopedro, Estela; Gutiérrez-Rodríguez, Pablo (Frontiers in Psychology, 2021)
Sports management is booming, thanks to society’s growing interest in sports in general. This work provides an exhaustive review of the scientific literature of one of the variables most coveted by managers: loyalty. Antecedents positively related to loyalty are also conceptualized in this paper. The scientific literature search was limited to the last 15 years to achieve a better fit with today’s context. The Web of Science database was the main search method used, along with other, secondary resources, for a total of 328 scientific articles obtained as a base for this review. The results of this study bring together the most representative data in a systematic review of the loyalty variable in the field of sports management: the antecedents of loyalty, the terms with the greatest presence in the theory, the most representative authors and sources of this topic, and so on. One of the most significant results obtained from the review of these 300 bibliographical references is that the factors to be borne in mind for marketing strategies in sports organizations are: satisfaction, commitment, trust and service quality. The literature reflects that these variables, present in studies on loyalty in general, can also be found in the literature on sports management – in particular, satisfaction and service quality. However, few papers include all these antecedents at once, making this an interesting field for future research.